Effects on vibration and surface roughness in high speed micro end-milling of Inconel 718 with minimum quantity lubrication - Abd. Rahman, Mohamed; Ali, Mohammad Yeakub; Khairuddin, Amir Saddam (IOP Publishing, 2017)
This paper presents the study on vibration and surface roughness of Inconel 718 workpiece produced by micro end-milling using Mikrotools Integrated Multi-Process machine tool DT-110 with control parameters; spindle speed (15000 rpm and 30000 rpm), feed rate (2 mm/min and 4 mm/min) and depth of cut (0.10 mm and 0.15mm). The vibration was measured using DYTRAN accelerometer instrument and the average surface roughness Ra was measured using Wyko NT1100. The analysis of variance (ANOVA) by using Design Expert software revealed that feed rate and depth of cut are the most significant factors on vibration meanwhile for average surface roughness, Ra, spindle speed is the most significant factor.